2015
DOI: 10.1002/ca.22546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical cardiac structural anatomy reconstructed within the cardiac contour using multidetector‐row computed tomography: Atrial septum and ventricular septum

Abstract: Cardiologists are increasingly becoming involved in procedures associated with the atrial septum and ventricular septum, such as transseptal puncture and selective site pacing. Moreover, detailed knowledge about the architecture of the atrial septum and ventricular septum is now available from studies by radiologists and anatomists. However, from the viewpoint of clinical cardiologists, many questions about the three-dimensional cardiac structural anatomy that relate closely to routine invasive procedures rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…B). This arrangement as seen in the mouse heart close to term is comparable to the situation found in the human heart, as shown by Mori and his colleagues in their study based on multidetector computed tomographic imaging (Mori et al, ). In the mouse heart, however, there are only two pulmonary veins opening to the left atrium, which enter caudally, adjacent to the left atrioventricular junction.…”
Section: Atrial Septationsupporting
confidence: 84%
See 1 more Smart Citation
“…B). This arrangement as seen in the mouse heart close to term is comparable to the situation found in the human heart, as shown by Mori and his colleagues in their study based on multidetector computed tomographic imaging (Mori et al, ). In the mouse heart, however, there are only two pulmonary veins opening to the left atrium, which enter caudally, adjacent to the left atrioventricular junction.…”
Section: Atrial Septationsupporting
confidence: 84%
“…We show that knowledge of normal development not only provides the necessary background for understanding septal defects, but is also for appreciation of relatively subtle features of the definitive postnatal septal structures. These can now be revealed in exquisite detail in the clinical setting by multidetector computed tomography, as described elsewhere in this special issue (Mori et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…As an adjunct to conventional techniques used to reveal these features,8–13 CT has now been shown to demonstrate in exquisite fashion the three-dimensional living anatomy of the atrial septum. This has shown that not all the lesions producing the potential for interatrial shunting are confined within the limits of the atrial septum 14. As we show in this review, such images now provide a much improved understanding of the relevant anatomy than can any diagrammatic schemes.…”
Section: Introductionmentioning
confidence: 91%
“…On the other side of the transverse sinus is found the non-adjacent aortic sinus of Valsalva (figures 1, 2 and 5). These anatomical alignments explain the potential risk of periprocedural complications,14 such as cardiac tamponade38 or production of fistulous communications with the non-adjacent aortic sinus 39. It is the proximity of the triangle of Koch to the anteroinferior rim of the oval fossa that determines the potential risk of injury to the atrioventricular conduction axis 14 40 41.…”
Section: Interventional Closure Of Oval Fossa Defectsmentioning
confidence: 99%
“…Virtual dissection also reveals the limited extent of the true atrial septum (Mori et al, ; Mori et al, ). The larger parts of the rims of the oval fossa are shown to be no more than folds between the right and left atrial walls.…”
Section: Assessing the Anatomy Of The Cardiac Componentsmentioning
confidence: 99%